The latest economic miracle ; Food and mouth diseasen ; The movie in his mind [videorecording] - Lazaro, Cheche (The Probe Team, 1995)
Philippine gross product according to FVR government and Mang Pandoy ; basic facts about foot and mouth disease ; and a closer look at the life and works of Armida Siguion Reyna.